Green synthesis of silver nanoparticles through oil: Promoting full-thickness cutaneous wound healing in methicillin-resistant Staphylococcus aureus infections - Wang, Yuhan; Li, Qinmei; Peng, Xiaomin; Li, Zheng; Xiang, Jun; Chen, Yunru; Hao, Kaiyuan; Wang, Shuaiyang; Nie, Dongyang; Cui, Yao; Lv, Feifei; Wang, Ying; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Due to the emergence of multi-drug resistant microorganisms, the development and discovery of alternative eco-friendly antimicrobial agents have become a top priority. In this study, a simple, novel, and valid green method was developed to synthesize Litsea cubeba essential oil-silver nanoparticles (Lceo-AgNPs) using Lceo as a reducing and capping agent. The maximum UV absorbance of Lceo-AgNPs appeared at 423 nm and the size was 5–15 nm through transmission electron microscopy result. The results of Fourier transform infrared and DLS showed that Lceo provided sufficient chemical bonds for Lceo-AgNPs to reinforce its stability and dispersion. The in vitro antibacterial effects of Lceo-AgNPs against microbial susceptible multidrug-resistant Escherichia coli (E. coli) and methicillin-resistant Staphylococcus aureus (MRSA) were determined. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of Lceo-AgNPs against E. coli were 25 and 50 μg/ml. The MIC and MBC of Lceo-AgNPs against MRSA were 50 and 100 μg/ml, respectively. The results of scanning electron microscopy showed that the amount of bacteria obviously decreased and the bacteria cells were destroyed by Lceo-AgNPs. In vivo research disclosed significant wound healing and re-epithelialization effects in the Lceo-AgNPs group compared with the self-healing group and the healing activity was better than in the sulfadiazine silver group. In this experiment, Lceo-AgNPs has been shown to have effects on killing multidrug-resistant bacteria and promoting wound healing. This study suggested Lceo-AgNPs as an excellent new-type drug for wound treatment infected with multidrug-resistant bacteria, and now expects to proceed with clinical research.